Systematic review of the impact of breast‐conserving surgery on cancer outcomes of multiple ipsilateral breast cancers. Issue 4 (22nd May 2018) - Winters, Z. E.; Horsnell, J.; Elvers, K. T.; Maxwell, A. J.; Jones, L. J.; Shaaban, A. M.; Schmid, P.; Williams, N. R.; Beswick, A.; Greenwood, R.; Ingram, J. C.; Saunders, C.; et al.
Abstract : Background: The clinical effectiveness of treating ipsilateral multifocal (MF) and multicentric (MC) breast cancers using breast‐conserving surgery (BCS) compared with the standard of mastectomy is uncertain. Inconsistencies relate to definitions, incidence, staging and intertumoral heterogeneity. The primary aim of this systematic review was to compare clinical outcomes after BCS versus mastectomy for MF and MC cancers, collectively defined as multiple ipsilateral breast cancers (MIBC). Methods: Comprehensive electronic searches were undertaken to identify complete papers published in English between May 1988 and July 2015, primarily comparing clinical outcomes of BCS and mastectomy for MIBC. All study designs were included, and studies were appraised critically using the Newcastle–Ottawa Scale. The characteristics and results of identified studies were summarized. Results: Twenty‐four retrospective studies were included in the review: 17 comparative studies and seven case series. They included 3537 women with MIBC undergoing BCS; breast cancers were defined as MF in 2677 women, MC in 292, and reported as MIBC in 568. Six studies evaluated MIBC treated by BCS or mastectomy, with locoregional recurrence (LRR) rates of 2–23 per cent after BCS at median follow‐up of 59·5 (i.q.r. 56–81) months. BCS and mastectomy showed apparently equivalent rates of LRR (risk ratio 0·94, 95 per cent c.i. 0·65 to 1·36). Thirteen studies compared BCS in women with MIBC versus those with unifocal cancers, reporting LRR rates of 2–40 per cent after BCS at a median follow‐up of 64 (i.q.r. 57–73) months. One high‐quality study reported 10‐year actuarial LRR rates of 5·5 per cent for BCS in 300 women versus 6·5 per cent for mastectomy among 887 women. Conclusion: The available studies were mainly of moderate quality, historical and underpowered, with limited follow‐up and biased case selection favouring BCS rather than mastectomy for low‐risk patients. The evidence was inconclusive, weakening support for the St Gallen consensus and supporting a future randomized trial. Abstract : This systematic review primarily compares clinical outcomes after BCS versus mastectomy for MF and MC cancers collectively defined as multiple ipsilateral breast cancers (MIBC). Only Six studies evaluated MIBC treated by BCS or mastectomy, with locoregional recurrence (LRR) rates of 2–23 per cent after BCS at median follow‐up of 59·5 (i.q.r. 56–81) months. BCS and mastectomy showed apparently equivalent rates of LRR (risk ratio 0·94, 95 per cent c.i. 0·65 to 1·36). One high‐quality study reported 10‐year actuarial LRR rates of 5·5 per cent for BCS in 300 women versus 6·5 per cent for mastectomy among 887 women. The available studies were mainly of moderate quality, historical and underpowered, with limited follow‐up and biased case selection favouring BCS rather than mastectomy for low‐risk patients. Breast‐conserving surgery feasible